Entrepreneurial Index of Farmers Applying Specialization and Diversification Farming System: Case Study of Vegetable Farmers in Kabupaten Agam - Almasdi Almasdi (International Journal of Agricultural Sciences, 2018)
The research aims to see the level of entrepreneurship of vegetable farmers in six sub-districts in Kabupaten Agam, particularly specialized and diversified vegetable farmer. The research is explanatory research, using 200 respondents taken by quota sampling proportionally. Farmer entrepreneurship level is measured using the Entrepreneurship Behavior Index (EBI). The result shows the overall level of entrepreneurship of vegetable farmers in six districts in Kabupaten Agam in the medium category that is equal to 69%,  Farmers who specialize in vegetable crops have higher levels of entrepreneurship than vegetable farmers who choose to diversified vegetable cultivation. The specialized vegetable farmer  have greater degree of decision making ability compared to diversified vegetable farmer. Diversified vegetable farmer concerned more on economic motives than specialized farmer. Risk taking ability also revealed difference tendency  among specialized and diversified vegetable farmer. Specialized vegetable farmer have bigger information seeking  capability, meanwhile diversified vegetable farmers are stronger for their leadership capability. The implications of this study that the entrepreneurial spirit vegetable growers is a variable that can provide reinforcement for the implementation of specialized cultivation systems. This means that if the entrepreneurial ability of farmers can be further improved, then with the application of specialized cultivation systems in vegetable crops, farmers will be able to create value-added products or produce derivative products from vegetable commodities produced.